MATERIAL BALANCE EQUATION FOR CO2 INJECTION IN ABNORMAL PRESSURE (SUBSIDENCE) GAS RESERVOIR - Clief Pattipawaej, Sandro
Reservoir performance and storage capacity are two crucial factors that must be estimated before conducting CO2 injection in the Carbon Capture and Storage (CCS) process. These factors can be estimated using a Material Balance equation for injection. The currently available Material Balance equation for CO2 injection is designed for injection into depleted normal pressure gas reservoirs. In this study, an Material Balance equation for CO2 injection into depleted abnormal pressure gas reservoirs was developed. Unlike the Material Balance equation for depleted normal pressure gas reservoirs, which have a constant Hydrocarbon Pore Volume (HCPV), the HCPV in depleted abnormal pressure gas reservoirs will change due to pressure variations during CO2 injection, necessitating a new Material Balance equation. The change in HCPV during injection can be expressed as a function of cumulative effective compressibility defined by Fetkovich, where this value can be calculated using production data with the Gan and Blasingame model. Several testing stages were conducted on the new Material Balance equation before CO2 injection simulation, including comparison with the Material Balance equation for injection into depleted normal pressure gas reservoirs, and testing by injecting the same gas as produced in Field X. The test results showed that the model we developed can mathematically transform into the existing model if HCPV is considered constant during production. Additionally, it was found that if the reservoir is reversible, the reservoir performance during injection of the same gas as produced is the same as the reservoir performance during production. In the CO2 injection simulation in Field X, a depleted abnormal pressure gas reservoir, it was found that the storage capacity of Field X for CO2 injection is larger compared to the total gas produced from the field. We also found that reservoir performance and the total amount of CO2 that can be injected are highly dependent on the compressibility of the gas mixture during injection. Based on the simulation, it is known that storage capacity depends only on the initial HCPV before production and the gas mixture composition after injection, so for the same initial HCPV, depleted abnormal pressure gas reservoirs and depleted normal pressure gas reservoirs will have the same storage capacity.